2003
DOI: 10.1002/ajmg.a.20374
|View full text |Cite
|
Sign up to set email alerts
|

Impact of BRCA1/2 testing and disclosure of a positive test result on women affected and unaffected with breast or ovarian cancer

Abstract: To evaluate the impact of BRCA1/2 testing and disclosure of a positive test result on women affected and unaffected with cancer. Longitudinal cohort study including women affected and unaffected with breast or ovarian cancer testing for a BRCA1/2 mutation. Data on well-being (anxiety, depression, cancer related distress, general health), treatment choice, and decision making about cancer prevention were collected at baseline (1 week after blood sampling; affected n = 192, unaffected n = 176) and at follow-up (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 26 publications
6
76
3
Order By: Relevance
“…Previous studies, which focused on the effects of revealing genetic susceptibility information to individuals with high family risk profiles for diseases have shown a mix of negative, positive, and null findings. [18][19][20][21][22][23][24][25][26] Even among DTC customers, previous research suggested that the population effects of such reports are largely insignificant but individuals may experience adverse emotional effects after learning about certain specific diseases' susceptibilities. 29 In an effort to draw causal inferences, this study supplemented previous research such as the REVEAL study, 20,24 which used a randomized block experimental design, to explore effect of learning about one's own genetic susceptibility to diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies, which focused on the effects of revealing genetic susceptibility information to individuals with high family risk profiles for diseases have shown a mix of negative, positive, and null findings. [18][19][20][21][22][23][24][25][26] Even among DTC customers, previous research suggested that the population effects of such reports are largely insignificant but individuals may experience adverse emotional effects after learning about certain specific diseases' susceptibilities. 29 In an effort to draw causal inferences, this study supplemented previous research such as the REVEAL study, 20,24 which used a randomized block experimental design, to explore effect of learning about one's own genetic susceptibility to diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing emotional responses, some studies indicate elevation in general or disease-specific distress in individuals after learning about their genetic susceptibility. These effects have been found for various time spans ranging from immediately after the results are given, 18 to weeks 19 and months 20 later. However, other studies found no such effects.…”
Section: Introductionmentioning
confidence: 93%
“…Positive BRCA1/BRCA2 results are associated with greater distress in women with breast cancer the closer they are to diagnosis. 53 Other studies have not reported any change in psychological risk with positive test results. 32,33,40,[57][58][59][60][61][62] Nonetheless, women who test positive for BRCA1/BRCA2 are also often met with resistance, shock, and other negative emotions from family members.…”
Section: Impact Of Genetic Test Resultsmentioning
confidence: 94%
“…Changes in psychological distress after testing in both affected (with cancer) and unaffected BRCA1/BRCA2 mutation carriers reflect mixed results. Some studies have demonstrated shortterm increases in anxiety levels 42,[53][54][55][56] in the first weeks to 1 month post-testing that return to baseline 12 months after testing. Positive BRCA1/BRCA2 results are associated with greater distress in women with breast cancer the closer they are to diagnosis.…”
Section: Impact Of Genetic Test Resultsmentioning
confidence: 99%
“…In a previous study of ours, we found that after blood sampling for genetic testing, women affected with breast or ovarian cancer reported a worse well-being and a lower preference for participation in decision-making than women without a previous history of cancer (Van Roosmalen et al, 2003). To explore a possible differential impact of the DA in women with and without a history of cancer, we examined interactions between the DA (and its timing) and history of cancer using the ANCOVA.…”
Section: Statistical Analysesmentioning
confidence: 99%